Peer-to-peer, community self-consumption, and transactive energy - Capper, Timothy (2022)
Capper, T., Gorbatcheva, A., Mustafa, M. A., Bahloul, M., Schwidtal, J. M., Chitchyan, R., Andoni, M., Robu, V., Montakhabi, M., Scott, I. J., Francis, C., Mbavarira, T., Espana, J. M., & Kiesling, L. (2022). Peer-to-peer, community self-consumption, and transactive energy: A systematic literature review of local energy market models. Renewable and Sustainable Energy Reviews, 162(July), 1-24. [112403]. https://doi.org/10.1016/j.rser.2022.112403